Original paperLow output syndrome following aortic valve replacement. Predictors and prognosis - Banach, Maciej; Goch, Aleksander; Misztal, Małgorzata; Rysz, Jacek; Barylski, Marcin; Jaszewski, Ryszard; Goch, Jan Henryk (Archives of Medical Science, 2007)
Introduction: Low output syndrome (LOS) is a dangerous postoperative complication, which significantly worsens the prognosis; it is an essential risk factor of postoperative death. The aim of the study was to analyze the predictors of postoperative low cardiac output syndrome in patients subjected to aortic valve replacement due to aortic stenosis or regurgitation. Material and methods: Three hundred (300) patients with significant isolated aortic valve defect due to either aortic stenosis (n=150) or regurgitation (n=150), who underwent isolated aortic valve replacement were included in the study. Low cardiac output syndrome (LOS) was defined as the need for high dosages of inotropic medication, and/or intra-aortic balloon pumping to sustain adequate hemodynamic status. Results: Postoperative low cardiac output syndrome was developed in 86 patients (28.6%), including 39 patients with aortic stenosis (26.0%) and 47 patients with aortic regurgitation (31.3%). We selected the following independent predictors of postoperative LOS (odds ratio in parentheses): (1) aortic stenosis group – advanced age (4.7), end-systolic (5.5) and end-diastolic intraventricular septum thickness (4.2) before the surgery, LVEF Ł50% (5.4) and insignificant mitral regurgitation (4.1) in the early postoperative period; (2) aortic regurgitation group – obesity (4.8), left ventricular end-systolic (4.5) and end-diastolic diameters (6.4) in the preoperative period and left ventricular end-systolic (4.7) and end-diastolic diameters (6.1), and left ventricular ejection fraction Ł50% (7.2) in the early postoperative period. Conclusions: The patients at high risk for the development of low cardiac output syndrome should be the focus of trials of new techniques of myocardial protection to effectively resuscitate the ischemic myocardium and optimization of preexisting heart failure symptoms.